1983
DOI: 10.1002/ajim.4700040123
|View full text |Cite
|
Sign up to set email alerts
|

Birth defects monitoring

Abstract: Population monitoring of birth defects provides a means for detecting relative changes in their frequency. Many varied systems have been developed throughout the world since the thalidomide tragedy of the early 1960s. Although it is difficult to pinpoint specific teratogenic agents based on rises in rates of a particular defect or a constellation of defects, monitoring systems can provide clues for hypothesis testing in epidemiological investigations. International coordination of efforts in this area resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Up to 70% of BDs could either be prevented, or with proper care, cured or ameliorated [23,24]. As the largest developing country in the world, a hospital-based surveillance system for monitoring BDs was established in China in 1986 [25].…”
Section: Discussionmentioning
confidence: 99%
“…Up to 70% of BDs could either be prevented, or with proper care, cured or ameliorated [23,24]. As the largest developing country in the world, a hospital-based surveillance system for monitoring BDs was established in China in 1986 [25].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated risks were observed for chromosomal defects as well as for cleft palatekleft lips. The combination of major malformations and the administration of insulin cannot be completely disregarded, but most authors view diabetes mellitus and not insulin as a risk factor [Cohen and Schenker, 1972;Miller et al, 1981;Mills, 1982;Molstedt-Pedersen, 1976;Soler et al, 19761. In the literature, mainly malformations of the musculoskeletal system, the nervous system, heart defects, and cleft palatekleft lips, as well as chromosomal aberrations, have been reported [Daw and Riley, 1984;Klingenberg et al, 1983;KuEera et al, 1965;Quaas et al, 1986;Schwaibold, 19851. Results obtained by our study therefore corroborate those reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Although the birth defects surveillance systems in the world provide invaluable data for descriptive and analytical epidemiologic studies, their effectiveness in detecting subtle epidemics has been criticized [Chen, 1979[Chen, , 1985Klingberg et al, 1983;Kä llén et al, 1984a;Khoury and Holtzman, 1987]. The classification of malformations used in monitoring has been discussed [Bod and Czeizel, 1981;Kä llén et al, 1984b;Holtzman and Khoury, 1986].…”
Section: Introductionmentioning
confidence: 99%